2016
DOI: 10.19030/jaese.v3i2.9845
|View full text |Cite
|
Sign up to set email alerts
|

iSTAR First Light: Characterizing Astronomy Education Research Dissertations In The iSTAR Database

Abstract: There is widespread interest among discipline-based science education researchers toKeywords: Astronomy Education Research; Science Education Literature Review rogress in astronomy education research-heretofore referred to simply as AER-requires that we first understand the scope of what is known about teaching and learning astronomy content across diverse settings, and what is not. Unfortunately, AER is a broad scientific discipline in which the existing landscape is particularly difficult to comprehensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Concerning publications of theses dissertations, in the USA there are about 500 published (Slater et al, 2016). In Brazil, even if not high in the overall ranking of education, we had an increase of AE in the last few years because of the support of financial agencies for Science Education.…”
Section: Achievements and Impacts Of Aer In The Last Decadesmentioning
confidence: 98%
See 1 more Smart Citation
“…Concerning publications of theses dissertations, in the USA there are about 500 published (Slater et al, 2016). In Brazil, even if not high in the overall ranking of education, we had an increase of AE in the last few years because of the support of financial agencies for Science Education.…”
Section: Achievements and Impacts Of Aer In The Last Decadesmentioning
confidence: 98%
“…All works and publications need to be surveyed, and the papers made available. One recent effort by Slater et al (2016) with the iSTAR Database is underway, but extensive work to get the works of many countries of the world remains, with the local language being a primary factor to overcome.…”
Section: Achievements and Impacts Of Aer In The Last Decadesmentioning
confidence: 99%
“…To understand the complexity of the discussions, we must address one key definition "Astronomy Education Research" (AER), which is empirical and theoretical research into the teaching and learning of astronomy content across diverse settings. It is a discipline which traverses the boundaries of other traditional fields, for example: astronomy, educa-tion and psychology (Slater et al (2016). Therefore, the individuals who work in the field of AER, are from a myriad of settings academic, industry, NGO and community organisations, which covers astronomers all the way to policy makers and beyond (Bailey and Lombardi (2015); Slater et al (2015)).…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative skills of these three individuals, allowed them to instigate what was to be called iSTAR (International STudies of Astronomy education Research) (Slater et al (2016)). A repository of AER in all its forms, from across the globe, thereby signifying that we live under a shared "sky", on a blue marble, whizzing around a middle-aged star, in a relatively "cool" galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Works are categorized by research method, nature of study-participants, educational learning venue studied, country and language of the study, and other fruitfully useful categories. The first domain of research artifacts ingested into the iSTAR database were doctoral dissertations (Slater et al, 2016). To the authors' great surprise, nearly 300 astronomy education research dissertations were found from the last 100-years.…”
mentioning
confidence: 99%